Learning And Learning Islamic Cultural History - Putri Nurfadillah, Ersa; Novela, Yolan; Alimni (JPT : Jurnal Pendidikan Tematik, 2020)
The ski learning process is teacher-oriented so that it appears active while students listen passively which results in low mastery of learning outcomes for the majority of students. This learning is expected to be able to increase the student's ability to learn so that the mastery of learning outcomes can be achieved by all students. This case study research, using a single approach includes teachers and students. Data collection techniques were carried out through interviews, observation. Teachers approach students so that teachers can better understand the abilities and characteristics of students, making it easier for teachers in the evaluation process. This conclusion shows that the lesson on thehistory of Islamic culture goes through the stages of planning for learning the history of Islamic culture, implementing learning, and evaluating learning. Each of these stages is carried out with fairly good criteria by the history teacher of Islamic culture. In the implementation of learning, teachers carry out learning with learning strategies that tend to be teacher-centered, so that the process of developing culture and national character still tends to emphasize aspects of knowledge (cognitive). From the evaluation aspect, there have not been many authentic assessment activities. These findings are believed by researchers as weaknesses in learning the history of Islamic culture.